Electric and Magnetic Field at the HV Substation during Lightning Strike - Markowska, R.; Sowa, A.; Wiater, J. (Elektronika ir Elektrotechnika, 2010)
This paper examines the electric and magnetic fields in an outdoor electric power substation 110/15 kV during lightning strike. The results of calculation were presented in time domain. Transient voltages can be easily measured or calculated for lightning conditions. Electric and magnetic field approximation is more complicated. There is no such easy method as for example digital oscilloscope to record transient electric or magnetic field in the air without any results disturbances. Electric and magnetic field determines inducted voltages and currents in HV circuits, so knowing it level could be useful to naturally prevent high transient voltages levels by changing devices agreement.